The Potential of using Biogas Feeding for Fuel Cells in Malaysia - Shafie, Shafini Mohd; Othman, Z.; Hami, N.; Omar, S. (International Journal of Energy Economics and Policy, 2019)
Malaysia as a tropical country is blessed with biomass resources that can be transferred to produce biogas. Despite its plentiful supply, biogas in Malaysia still has not been fully optimised as only a small fraction of biomass from oil palms are currently being processed to produce biogas. This paper aims to identify the potential use of biogas to be fed to fuel cells, and determine the conservation of conventional resources and reduction of carbon dioxide (CO2) emissions in electricity generation. Annually, Malaysia potentially consumes biogas for feeding to fuel cells and this electricity generation can reach up to 972 MW. By 2030, it is predicted that this palm oil residue can potentially generate about 1474 MW, which is almost a 50% increment. The penetration of palm oil residue in feeding to the fuel cell system could reduce Malaysia’s CO2 emissions per year. The support from all stakeholders is needed in order to generate electricity using this new method. Keywords: Biogas, Fuel Cell, Palm Oil Residue, Malaysia JEL Classifications: Q42, R11 DOI: https://doi.org/10.32479/ijeep.8373